2015
DOI: 10.1002/smr.1721
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors affecting decision outcome and lead time in large‐scale requirements engineering

Abstract: Lead time, defined as the duration between the moment a request was filed and the moment the decision was made, is an important aspect of decision making in market-driven requirements engineering. Minimizing lead time allows software companies to focus their resources on the most profitable functionality and enables them to remain competitive within the quickly changing software market. Achieving and sustaining low decision lead time and the resulting high decision efficiency require a better understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…Looking at security QFs after 13Q1, it appears to be a similar pattern in the decision making of high acceptance ratio of security QFs that are demanded by external stakeholders. This is similar to our previous work where we found that change requests proposed by external stakeholders are more likely to be accepted (Wnuk et al, 2015). Looking at releases 14Q2 to 15Q2, we observe that important external stakeholder QFs are discarded.…”
Section: Acceptance Ratio Across the Stagessupporting
confidence: 90%
See 2 more Smart Citations
“…Looking at security QFs after 13Q1, it appears to be a similar pattern in the decision making of high acceptance ratio of security QFs that are demanded by external stakeholders. This is similar to our previous work where we found that change requests proposed by external stakeholders are more likely to be accepted (Wnuk et al, 2015). Looking at releases 14Q2 to 15Q2, we observe that important external stakeholder QFs are discarded.…”
Section: Acceptance Ratio Across the Stagessupporting
confidence: 90%
“…Furthermore, they discovered that 19% of all QRs are dismissed at some stage before release. In previous work, we have found that change requests from external stakeholders are more likely to be accepted (Wnuk, Kabbedijk, Brinkkemper, Regnell, & Callele, 2015). We have previously concluded that features proposed late in the release cycle are more often rejected than accepted (Wnuk et al, 2015).…”
Section: Tablementioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, criteria need to be prioritized. Similar reflections were presented in the field of requirements engineering, where it was found that more complex decisions take more time [35]. As a consequence requirements triage has been introduced that removes the most obvious options first to avoid investigative effort [36].…”
Section: Criteria (Rq13)mentioning
confidence: 73%
“…These 2 requirements, SUPL122 and UC16, refine ( trace‐from ) the feature FEAT25 in Figure . All the features in the VIS document have been redefined as requirements during the analysis process to prepare the software design …”
Section: A Requirements Engineering Tool For Global Software Engineeringmentioning
confidence: 99%